PENGARUH PENYULUHAN GIZI TENTANG MAKANAN BERAGAM BERGIZI SEIMBANG DAN AMAN MELALUI BUKU CERITA BERGAMBAR TERHADAP PENINGKATAN PENGETAHUAN DAN SIKAP ANAK SEKOLAH DASAR NEGERI 060895 MEDAN - Rodhia Ramadhani; Albiner Siagian; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
The increasing prevalence of malnutrition and overnutrition in Primary School student need a serious handling. One of the intervention isnutritional education using the media which interesting for Primary School student. Giving information about various nutritional balance and secure foods is one strategy to increase the knowledge and attitude of students to choose the various nutritional balanced and secured foods in their daily menus. The aim of this research to find out the effect of nutritional education through ilustrated story book to increase the knowledge and attitude of primary student of SDN 060895 Medan diet healthy. The type of this research is quasi experimental with one group pretest posttest design. Total sample are 71 children which fluently to reading. Treatment was giving infromation by ilustrated story books. Measurement was taken twice, before and after getting education nutrition.  Analysis of data using statistical test using Paired sample t- test for knowledge and Willcoxon for attitude with significant level of 95 %. The result showed that children given knowledge ilustrated story book pretest scores of elementary student in adequate category (15,5%) and posttest adequate category being  (76,1%). Attitude before intervention pretest category (45,1%) and after intervention posttest category (69%). Statistical analysis showed there were differences in knowledge and attitude scores after nutrition education through ilustrated story book (p = 0,000). The conclusion of this research there were the effect of nutritional education through illustrated story book for the primary school students knowledge and attitude about various nutritional, balanced, and secured food. Suggestions of this research was for the local health department to more attention about nutritional counseling in the school, and for the nutrition workers in community health centers to use illustrated story book to inform about various nutritional, balanced and secured to primary school student with more interesting concept. Keywords : balance diet, illustrated story book, knowledge,  attitude, primary school student.